2012
DOI: 10.1101/gad.202242.112
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle gene-specific control of transcription has a critical role in proliferation of primordial germ cells

Abstract: Transcription elongation is stimulated by positive transcription elongation factor b (P-TEFb), for which activity is repressed in the 7SK small nuclear ribonucleoprotein (7SK snRNP) complex. We show here a critical role of 7SK snRNP in growth control of primordial germ cells (PGCs). The expression of p15 INK4b, a cyclin-dependent kinase inhibitor (CDKI) gene, in PGCs is selectively activated by P-TEFb and its recruiting molecule, Brd4, when the amount of active P-TEFb is increased due to reduction of the 7SK s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 34 publications
(35 reference statements)
2
15
0
Order By: Relevance
“…In particular, the significant SNP in the vicinity of the 7SK gene on BTA10 relates to small RNA that are important for the regulation of transcription. Our significant result stays in line with experimental findings by Okamura et al (2012), who demonstrated a role of small RNA in the proliferation of germ cells in mouse embryos. The gene PAPPA on BTA8, with a significant effect on the number of spermatozoa estimated for rs109336730 located within an intron of this gene, codes for a pregnancy-associated plasma protein A and is thus related to female fertility.…”
Section: Discussionsupporting
confidence: 95%
“…In particular, the significant SNP in the vicinity of the 7SK gene on BTA10 relates to small RNA that are important for the regulation of transcription. Our significant result stays in line with experimental findings by Okamura et al (2012), who demonstrated a role of small RNA in the proliferation of germ cells in mouse embryos. The gene PAPPA on BTA8, with a significant effect on the number of spermatozoa estimated for rs109336730 located within an intron of this gene, codes for a pregnancy-associated plasma protein A and is thus related to female fertility.…”
Section: Discussionsupporting
confidence: 95%
“…LncRNAs which are generated in intronic, intergenic, antisense loci or overlapping regions play a great role in diverse gene regulatory functions (37,38). At present, numerous studies have demonstrated that lncRNAs are involved in tumor carcinogenesis since it can accelerate cell proliferation through controlling correlative proteins (39)(40)(41). In the present study, we found that the expression levels of lncRNA-SNHG7 mRNA and protein obviously increased in lung cancer tissues compared to adjacent non-cancerous tissues.…”
Section: Discussionsupporting
confidence: 50%
“…Previous studies have found associations of the 7SK variants with traits related to fertility and sexual precocity in bull and cattle, respectively (Melo et al, ; Suchocki & Szyda, ). Also, it has been demonstrated that this candidate gene has an important role on the control of primordial germ cell proliferation of mouse embryos (Okamura et al, ). SMG9 is another candidate gene in this selection region on ECA10.…”
Section: Discussionmentioning
confidence: 99%